EDUKASI PENTINGNYA PENDIDIKAN ANAK USIA DINI PADA IBURUMAH TANGGADUSUN TANON KLUPUTAN, DESA KENAIBAN, JUWIRING, KLATEN, JAWA TENGAH - Siti Hapsah Isfardiyana (Asian Journal of Innovation and Entrepreneurship, 2014)
Usually, children in Tanon-Kluputanvillagespend their time playing andhave lessmotivated to learning. In addition, most parents do not get formal education leads to alack of knowledge regarding child education development clinically. In fact, EarlyChildhood Education (ECD) is one of the optimal education period and need to beconsidered by parents. But in reality, there are still many people who do not know theimportance of early childhood educational programs. The program to socialize theimportance of early childhood education in housewives Tanon Kluputan Hamlet, VillageKenaiban is very important to do. The purpose of the implementation of thisprogram isto increase the understanding of mothers about the importance of early childhoodeducation as well as to motivate parents to encourage their children can also improvethe academic achievement of children Dukuh Kenaiban.